2017
DOI: 10.4236/ojmp.2017.64017
|View full text |Cite
|
Sign up to set email alerts
|

Professional Stress Factor of Vulnerability in Which Has Occurred of the Road Traffic Accidents at a Sample of Drivers in Morocco

Abstract: The professional stress is a physical and emotional harmful reaction. In fact, it presents a major public health problem in Morocco. Our work is directed to study the differences between the various groups of professional and nonprofessional drivers in terms of stress reactions, noise nuisance and implication in the production accidents. The present study is transversal descriptive type based on a questionnaire and neuropsychological tests conducted by 60 nonprofessional drivers and 60 taxi drivers in Kenitra.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…There was a prevalence of 46.8% for a high level of perceived stress among motorcycle taxi drivers, a high estimate compared to non-professional drivers (22.3%) and lower than that observed among taxi drivers (63.3%), both from Morocco ( 25 ) . Brazilian and international studies on perceived stress in motorcycle taxi drivers were not identified, which made comparisons with the findings of the present study difficult.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…There was a prevalence of 46.8% for a high level of perceived stress among motorcycle taxi drivers, a high estimate compared to non-professional drivers (22.3%) and lower than that observed among taxi drivers (63.3%), both from Morocco ( 25 ) . Brazilian and international studies on perceived stress in motorcycle taxi drivers were not identified, which made comparisons with the findings of the present study difficult.…”
Section: Discussionmentioning
confidence: 65%
“…The items are composed of a four-point Likert scale (strongly agree to strongly disagree). Excessive commitment was dichotomized into “absent” and “present”, using the median cut-off point ( 25 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Evidenciou-se prevalência de 46,8% para alto nível de estresse percebido entre os mototaxistas, estimativa elevada em comparação a motoristas não profissionais (22,3%) e inferior à observada entre taxistas (63,3%), ambos do Marrocos (25) . Estudos brasileiros e internacionais sobre o estresse percebido em mototaxistas não foram identificados, o que dificultou comparações com os achados do presente estudo.…”
Section: Discussionunclassified
“…Os itens são compostos por escala Likert de quatro pontos (concordo totalmente a discordo totalmente). O comprometimento excessivo foi dicotomizado em "ausente" e "presente", tendo como ponto de corte a mediana (25) .…”
Section: Protocolo Do Estudounclassified